MANAJEMEN STRATEGI PADUAN SUARA DI SMA KRISTEN EBEN HAEZAR MANADO - Serafim A. Harikusuma; Erwin Sianturi (Institut Agama Kristen Negeri Manado, 2020)
Abstract This study aims to describe the management of choir strategies in Kr. Eben Haezar Manado. This research is a qualitative research with descriptive method. Location of research in SMA Kr. Eben Haezar Manado, in 2018. Methods of data collection are observation, interviews and documentation. From the results of data analysis and interpretation, indications are obtained that: (1) The elements of strategy management that support the success of choir management are Man, Money, Method, Material, and Market. (2) Choir strategy management in SMA Kr. Eben Haezar Manado goes well. The strategy planning process is carried out by the management with guidance and input from the coaches and the coaches, and with supervision from the Eben Haezar Manado Foundation. From these findings, it is recommended that the management of Benzar Choir should make a written organizational structure in order to facilitate the affairs of the Benzar Choir data archive, and arrange the composition of the board by appointing coordinators so that they can help carry out better planned management of the strategy